STRES KERJA DI PT. X SEMARANG DITINJAU DARI PEKERJAAN MONOTON - Yohanes Paijanto; Puspita Puji Rahayu (IMAGE, 2023)
This research aims to see the relationship between monotonous work and work stress carried out by PT employees. X Semarang. Work stress here is meant by stress that often occurs in the workplace. One of the causes of work stress is monotonous work at work, which employees do every day. This research was conducted at PT. This research uses two variables, namely monotonous work and work stress. The research used a monotonous work scale consisting of 22 valid items with a reliability coefficient value of 0.903 and a work stress scale of 21 valid items with a reliability coefficient value of 0.814. The data analysis technique uses product moment correlation with the help of SPSS 26 statistics. The results of the research show that the sig (2-tailed) correlation test value is 0.42 (p < 0.05) indicating that the independent variable monotonous work has a significant relationship with the dependent variable work stress. Which means that there is a positive relationship between monotonous work and work stress, namely the higher the monotonous work, the higher the work stress. Monotonous work makes an effective contribution to work stress of approximately 37.3%. Keywords: Job Stress and Monotonous Work